Exploring the Digital Entrepreneurship Ecosystem in Indonesian Higher Education: Barriers, Enablers, and Strategic Empowerment - Sholihah, Masyithoh Annisaush; Saputri , Isna Ajeng; Istiqomah, Nabila (SAFE-Network, 2025)
This study explores the configuration of digital entrepreneurship ecosystems in Indonesian higher education institutions (HEIs), emphasizing barriers and enabling factors that shape students’ entrepreneurial engagement. Using an explanatory sequential mixed-methods design, the research integrates quantitative survey data (N = 173) and qualitative interviews to examine entrepreneurial readiness, innovation capacity, and institutional support structures. Findings indicate that students demonstrate high motivation and self-efficacy but face persistent constraints related to mentorship, funding, and technical access. The qualitative phase identifies six recurring challenges—ideation and market-fit, marketing skills, time management, mentoring gaps, technical limitations, and financial barriers—revealing a fragmented yet promising ecosystem. To address these issues, the study proposes the Strategic Empowerment Model for Digital Entrepreneurship (SEM-DE), a four-lever framework emphasizing structured ideation, continuous mentoring, skill-based clinics, and micro-grant schemes. This research contributes a contextualized and actionable model for strengthening university-based entrepreneurship ecosystems and informs policy directions toward inclusive, innovation-driven higher education in emerging economies.